Burkitt's Lymphoma Mimicking a Primary Gynecologic Tumor - Szu-Ching Lu; Wan-Lin Shen; Ya-Min Cheng; Chen-Yang Chou; Pao-Ling Kuo (Taiwanese Journal of Obstetrics & Gynecology, 2006)
Objective: Burkitt's lymphoma (BL) occurs mostly in children; bilateral ovarian involvement mimicking a gynecologic malignancy in adults is extremely rare. Here, we report a patient with BL mimicking a gynecologic tumor Case Report: A 50-year-old Taiwanese woman presented with the complaint of persistent lower abdominal distension with dull pain, easy satiety, and progressively increasing abdominal girth for 2 weeks. Amenorrhea was also noted for about 2 months, and her review of systems was negative for the common “B” symptoms associated with lymphoma. At our hospital, imaging studies revealed a huge pelvic mass (10.8 ×8.7 cm), suggesting a large subserous myoma or an ovarian tumor. Under the impression of pelvic mass, she underwent exploratory laparotomy. Primary ovarian sex-cord malignancy with cecum involvement was impressed by the primitive intraoperative frozen section report. Subsequently, an optimal cytoreductive operation with right hemicolectomy was performed. However, final histopathologic report was an extranodal multifocal BL. Conclusion: Although extranodal BL in ovaries is a rare condition, it should be noted in the differential diagnosis of pelvic gynecologic malignancies.